The use of sansevieria sp and cymbopogon nardus extracts on humidifier modification to reduce airborne germs - Rachmaniyah Rachmaniyah; Rusmiati Rusmiati; Khambali Khambali (International Journal of Public Health Science (IJPHS), 2022)
It turns out that indoors is not 100% safe from harmful pollutantsThere was even a special study that examined Sick Building Syndrome. Other factors that also play a role are occupant activities, building materials, furniture and equipment, as well aindoor temperature/humidity. Therefore, an alternative technology is needed to control room air quality, in this case is a humidifier filled with natural ingredients such as mother-in-law's tongue (Sansevieriasp) and lemongrass (CymbopogonNardus) extracts. This study aimed to evaluate the chemical composition and potential of Sansevieriasp and CymbopogonNardus as anti-fungal and anti-germ substances in a room. Sansevieria sp and Cymbopogon Nardus extract can be aromatherapy that prevents sick building syndrome. This study used an experimental method and One Group Pre-test Post-test Design. In this case, ansevieria sp and Cymbopogon Nardus extract were used as humidifier modification material to reduce airborne germ. Sansevieria extract was provided atconcentrations of 30%, 40%, and 50%. Furthermore, the data analysiswas conducted through Anovatest.Based on the effectiveness test that has been done, it showed that the Sansevieriaspand Cymbopogon Nardus extracts at concentration of 30% decreased the germs by 78.2%, while at the concentration of 40%, it decreased the indoor air germs by 74.2%, and at the concentration of 50%, it decreased the germs by 65.11%. Furthermore, the results of the Anova test showed that the Sansevieria,sp extracts at the concentration of 30% 40%, and 50% had a p-value > 0.05. It means that there was no significant or insignificant difference between the concentrations employed so that in this study, the extracts of Sansevieriaspand Cymbopogon Nardus extracts had the same effective antibacterial power. Based on the results, it was concluded that Sansevieria spand Cymbopogon Nardusextract as modified humidifier solution at concentrations of 30%, 40%, and 50% have the same effectiveness in reducing the Germ in the room air.